City-level SARS-CoV-2 sewage surveillance. (November 2021) - Yaniv, Karin; Shagan, Marilou; Lewis, Yair E.; Kramarsky-Winter, Esti; Weil, Merav; Indenbaum, Victoria; Elul, Michal; Erster, Oran; Brown, Alin Sela; Mendelson, Ella; Mannasse, Batya; Shirazi, Rachel; et al.
Abstract: The COVID-19 pandemic created a global crisis impacting not only healthcare systems, but also economics and society. Therefore, it is important to find novel methods for monitoring disease activity. Recent data have indicated that fecal shedding of SARS-CoV-2 is common, and that viral RNA can be detected in wastewater. This suggests that wastewater monitoring is a potentially efficient tool for both epidemiological surveillance, and early warning for SARS-CoV-2 circulation at the population level. In this study we sampled an urban wastewater infrastructure in the city of Ashkelon (̴ 150, 000 population), Israel, during the end of the first COVID-19 wave in May 2020 when the number of infections seemed to be waning. We were able to show varying presence of SARS-CoV-2 RNA in wastewater from several locations in the city during two sampling periods, before the resurgence was clinically apparent. This was expressed with a new index, Normalized Viral Load (NVL) which can be used in different area scales to define levels of virus activity such as red (high) or green (no), and to follow morbidity in the population at the tested area. The rise in viral load between the two sampling periods (one week apart) indicated an increase in morbidity that was evident two weeks to a month later in the population. Thus, this methodology may provide an early indication for SARS-CoV-2 infection outbreak in a population before an outbreak is clinically apparent. Graphical abstract: Image 1 Highlights: Detecting the presence of SARS-CoV-2 virus RNA in urban wastewater. The city sewer system may provide an early warning for SARS-CoV-2 outbreaks. Urban wastewater monitoring allows to target specific location as a morbidity center. This technique reduce wastewater dilution effect while using direct RNA extraction. NVL index defines various infected urban zones from red (high) to green (low).